2012
DOI: 10.1111/j.1365-2699.2012.02696.x
|View full text |Cite
|
Sign up to set email alerts
|

Species formation and geographical range evolution in a genus of Central American cloud forest salamanders (Dendrotriton)

Abstract: Aim  Montane Central America offers an ideal system for testing geographical hypotheses of species diversification. We examined how the complex geological history of Nuclear Central America has shaped the diversification of a genus of cloud‐forest‐inhabiting salamanders (Dendrotriton). We applied parametric models of geographical range evolution to determine the predominant mode of species formation within the genus and to test existing hypotheses of geographical species formation in the region. Location  Mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…The uplifting of highlands on either side of the MPJ system fault area, and its further entrenchment producing isolation among populations, has generated divergence events in both lowland and highland species (but see Rovito et al. ,b). However, the timings of the divergence events associated with isolation by the MPJ barrier fall within the Miocene, Pliocene and Pleistocene.…”
Section: Discussionmentioning
confidence: 99%
“…The uplifting of highlands on either side of the MPJ system fault area, and its further entrenchment producing isolation among populations, has generated divergence events in both lowland and highland species (but see Rovito et al. ,b). However, the timings of the divergence events associated with isolation by the MPJ barrier fall within the Miocene, Pliocene and Pleistocene.…”
Section: Discussionmentioning
confidence: 99%
“…Dendrotriton achieves highest species diversity in the Maya highlands, with only a single species found in the Guatemalan Volcanic Cordillera and another species found on the isolated Montaña de Santa Bárbara in the Chortís highlands. Biogeographic analyses with LAGRANGE indicated that Dendrotriton most likely arose in the Sierra Madre de Chiapas and/or the Sierra de los Cuchumatanes, both part of the Maya highlands, and subsequently dispersed to the Chortís highlands (Rovito et al ., ). Even though three species of Cryptotriton are found in the Maya highlands, two of these are from Alta Verapaz and are very close to the Motagua fault zone; no Cryptotriton is known from the Sierra de los Cuchumatanes or the Sierra Madre de Chiapas.…”
Section: Discussionmentioning
confidence: 97%
“…Chiropterotriton , as currently recognized, occurs exclusively to the west of the Isthmus of Tehuantepec and is not closely related to species it formerly contained that are now allocated to other genera ( Cryptotriton, Dendrotriton , and Nototriton ). Molecular studies using both allozymes (Good & Wake, ; Darda, ; Vásquez‐Almazán et al ., ) and DNA sequence data (García‐París & Wake, ; Parra‐Olea, ; Townsend et al ., ; Rovito et al ., ) have shed light on relationships within and between genera and supported the recognition of many new species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction with bromeliads have been particularly important in the evolution and ecology of several Neotropical amphibian groups (e.g. [7], [12], [13], [14]). Several bromeliad traits are associated with the presence of anurans, including humidity, water availability and phytotelmata size [15]–[18].…”
Section: Introductionmentioning
confidence: 99%